2002
DOI: 10.1159/000065186
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Locus coeruleus Neuronal Activity by Interleukin-1 and the Involvement of Endogenous Corticotropin-Releasing Hormone

Abstract: Activity of the locus coeruleus (LC), which is the source of most of the norepinephrine in the brain, may participate in effects of the cytokine interleukin (IL)-1. This report describes the influence of IL-1β on the electrophysiological single-unit activity of LC neurons. When microinjected into the LC, human recombinant IL-1β (50 pg to 5 ng) increased the activity of LC neurons, predominantly by increasing ‘burst’ firing, which occurs in response to a sensory stimulus. At the higher doses and/or with longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 84 publications
(111 reference statements)
2
23
0
Order By: Relevance
“…For instance, the electrophysiological activity of LC neurons is increased following an acute immune challenge (Borsody & Weiss, 2002;2004;. Accordingly, we show in the present study that the LC displays intense c-Fos labeling 6 hours following LPS injection.…”
Section: Lps Induces Delayed Cellular Activities In the Extended Amygsupporting
confidence: 70%
“…For instance, the electrophysiological activity of LC neurons is increased following an acute immune challenge (Borsody & Weiss, 2002;2004;. Accordingly, we show in the present study that the LC displays intense c-Fos labeling 6 hours following LPS injection.…”
Section: Lps Induces Delayed Cellular Activities In the Extended Amygsupporting
confidence: 70%
“…Serum-containing medium used in the present study could confer to the neurons the ability to respond to IL-1 ␣ as well as IL-1 ␤ , but could also contribute to neurons being partially depolarised in the presence of IL-1, which could then lead to release of IL-1-induced IL-6. It is well documented that IL-1 induces neuronal depolarisation [20,21] , and other studies also found that IL-1 can lead to synthesis and release of IL-6 from rat hippocampal neuronal cell lines [22] and mouse cortical neurons [18,19,23] . Collectively, these observations demonstrate that the external environment tightly controls neuronal responses to IL-1 and that subtle changes in the culture condition can lead to a change in the neuronal response to IL-1.…”
Section: Discussionmentioning
confidence: 85%
“…The activity of the locus ceruleus (LC), which is the most important source of noradrenaline inside the brain, was increased after in vivo IL-1 ␤ microinjection in this area; this effect was blocked by IL-1 ␤ receptor antagonist (IL-1 RA) [55,56] . Furthermore, microinjection of IL-1 RA alone was found to decrease LC activity, raising the possibility that LC neurons are under the influence of tonic excitation by IL-1 ␤ [55] .…”
Section: Il-1 ␤ and Il-1 ␣mentioning
confidence: 99%